2020
DOI: 10.21894/jopr.2020.0075
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION DENSITY OF Elaeidobius kamerunicus Faust IN DIFFERENT SPIKELET POSITION AT ANTHESISING MALE INFLORESCENCE OF Elaeis guineensis Jacq. IN SABAH AND SARAWAK, MALAYSIA

Abstract: The oil palm male inflorescences provide food source and breeding sites for the pollinating weevil, Elaeidobius kamerunicus (E. kamerunicus). The present study examined the difference in the formation of the oil palm male inflorescences on different soil types, and how the differences affect the population density of E. kamerunicus. Samplings of adult E. kamerunicus and the spikelets of fully-anthesising oil palm male inflorescences were conducted monthly for a period of 18 months at four oil palm plantations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Ref. [ 92 ] suggested that longer spikelets provide more breeding sites and food sources for the weevils. Insufficient male inflorescences may contribute to a decline in the E. kamerunicus population and reduce pollination activity, leading to poor fruit set production [ 89 ].…”
Section: Inadequate Pollen Deposition and Pollen Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Ref. [ 92 ] suggested that longer spikelets provide more breeding sites and food sources for the weevils. Insufficient male inflorescences may contribute to a decline in the E. kamerunicus population and reduce pollination activity, leading to poor fruit set production [ 89 ].…”
Section: Inadequate Pollen Deposition and Pollen Qualitymentioning
confidence: 99%
“…[ 118 ] reported that the distribution of rainfall even a month prior to the data collection impacts the flight activity of E. kamerunicus on male inflorescences, especially with rain levels exceeding 500 mm. Changes in the number of rainy days can also alter the pollinating activity of E. kamerunicus since it reduces the pollen load and its viability [ 92 ]. Furthermore, pollen viability is also affected during rainy days.…”
Section: Climate and Weather Drivermentioning
confidence: 99%
See 2 more Smart Citations
“…Kouakou et al [ 18 ] reported that the population abundance of the pollinator weevil is strongly related to the production of the oil palm fruit-set. Male and female inflorescences both emit a distinctive aniseed scent to attract the EK pollinator for pollination [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%